Effect of Coffee Pulp Compost and Terrace on Erosion, Run off and Nutrients Loss from Coffee Plantation in Lahat Regency, South Sumatra - Bernas, Siti Masreah (JOURNAL OF TROPICAL SOILS, 2011)
On some coffee plantations in Lahat Regency South Sumatra, in some places the farmers did not apply agricultural practices, such as tillage, conservation practices, and fertilizers. Many researches have been done to study about effects of organic fertilizer on soil nutrients content and plant growth as well as and the impacts of terrace on soil water content, run-off and erosion. However, there was less research in the highland area. Whereas the possibilityof run off, erosion and nutrient leaching the high land area was high. Thus, it was important to apply terrace and organic coffee pulp in this farm. The aims of this research were to determine the effect of terrace and organic fertilizer on run off and soil erosion, nutrients loss and nutrient content in coffee leaves. Terrace system and organic fertilizer were applied on a one year old coffee plantation in Lahat Regency. Before the treatment applied,coffee pulp as organic fertilizer was decomposed in the chamber for about 2 months. The experiment was conducted in factorial in a Randomized Block Design with two factors. The first factor was coffee pulp compost (0, 3, and 6 Mg ha-1), and the second factor was type of terrace (without, individual, and bund terraces). The size of each plot was 2 m width and 10 m length. Data was analysed by using LSD (Least Significant Different) test. The resultshows that bund terrace reduced runoff and erosion significantly up to 79% (for run off water) and 78% (for eroded soil) compared to without terrace. Organic fertilizer did not affect run off and soil erosion. This may be caused by properties of coffee pulp compost which were fine particulates and the dosages of application were too low to cover soil suface. Bund terrace decreased significantly N, P, K nutrients in soil loss (sediment). The amount of N losswas reduced from 3.37 kg ha-1 per four months (without terrace) to about 0.75 kg ha-1 per four months (bund terrace). Terrace and organic fertilizer did not affect significantly nutrients content in the leaves, but P-content was low without organic fertilizer addition. It is suggested to apply bund terrace and higher organic fertilizer dose on the coffee farm, and further experiments when harvesting the yield (berries) are needed for the second year oldcoffee farm.Keywords: Coffee, compost, erosion, nutrient, pulp, terrace